MEMBANGUN SISTEM APLIKASI HUTANG PIUTANG PADA KOPERASI KARYAWAN MAKMUR NIAGA PT. WIKA BETON SUMUT, Tbk SEBAGAI SOLUSI MENGHINDARI KESALAHAN PENCATATAN - Agayasa, Ayuni Rezky; Hajijah, Hajijah; Arliana, Lina; Pasaribu, Tio Ria (Majalah Ilmiah Kaputama, 2017)
The development of technology is currently growing rapidly, this requires every company to continue to improve the system used for the management of its business. Expected in each field using the computerized system. No exception in the field of accounts payable. In the Commercial Employees Cooperative Makmur Wika Beton Sumatra, tbk accounts payable data management is still manual and very likely there was an error in the recording. The number of tables of contents and folders different storage places is very influential on the data inputting error. Accounts payable so the data is very vulnerable to errors and data becomes invalid. The authors felt the need to discuss the management of data on goods production accounts payable so the future can be computerized. Each transaction is concerned with accounts payable starting from ordering goods, until payment of accounts payable will be processed and stored disistem. The system will be discussed in this thesis is a system that is able to manage every transaction accounts payable for goods production that occurred in the Commercial Employees Cooperative Makmur . With a computerized system admin will be able to manage data Kopkar payable as easily as searching the details of the data based on the number spb faster , the possibility of duplicate data can be solved , as well as the report clearly displays the classification of loans receivable based on the number spb.